Imaging of Madura foot: Case report - Asmae Rais; Nizar El Bouardi; Zined Bouanani; Amal Akammar; Meriem Haloua; Badreddine Alami; Moulay Youssf Alaoui Lamrani; Meryem Boubbou; Mustapha Maaroufi (Radiology Case Reports, 2024)
The case presented illustrates a very rare chronic granulomatous disease called the Madura foot or also called mycetoma. It is a chronic granulomatous disease, caused by a contained infection that penetrates the subcutaneous tissues and spreads to the nearby bone by damaging the affected area's vascularization. Early diagnosis is greatly aided by clinical history and imaging, especially if the “dot-in-circle” sign—a pathognomonic marker of mycetoma—is seen on the MRI. Compared to ordinary radiographs, computed tomography offers a more accurate study of changes in the bone. In order to apply the appropriate course of treatment, it is critical to identify the causal species, which can be caused by either a true fungus (eumycetoma) or a bacterium Actinomyces (Actinomycetoma). Treatment can be extremely challenging and can even result in amputation, particularly if the diagnosis is delayed.